Patella Tendon Injuries Secondary to Cement Spacers Used at First-Stage Revision of Infected Total Knee Replacement - Wilson, Katherine; Kothwal, Rahul; Khan, Wasim S.; Williams, Rhodri; Morgan-Jones, Rhidian (Frontiers in Surgery, 2015)
We describe a series of three patients who sustained patella tendon injuries in infected TKAs following the use of a static cement spacer at first-stage knee revision. The patella tendon injuries resulted in significant compromise to wound healing and knee stability requiring multiple surgeries. The mid-term function was poor with an Oxford score at 24 months ranging from 12-20. Based on our experience, we advise caution in the use of static cement spacer blocks. If they are to be used, we recommend that they should be keyed in the bone to prevent patella tendon injuries.